Image Indexing System Using Texture Mining - Patwal, Pratap Singh; Tyagi, Jitendra Kumar; Yadav, Garima (International Journal of Computer Sciences and Engineering, 2025)
The aim of this research to work on new methods of image feature extraction, image retrieval and feature vector indexing. This research work presents a new weighted histogram based statistical features, which integrate the pixel spatial distribution information into a numerical value. As a fundamental retrieval method, it can easily be integrated with multidimensional R- Tree indexing method. The experiment results show that this method is still effective when the data scale is very large, and it has superior scalability than traditional indexing methods. We analyzed the performance of the system under four classes of different database environment.